2015
DOI: 10.1109/jlt.2015.2456239
|View full text |Cite
|
Sign up to set email alerts
|

Optical Gradient Waveguides in Photo-Thermo-Refractive Glass Formed by Ion Exchange Method

Abstract: Photo-thermo-refractive (PTR) glasses are the class of polyfunctional materials that combine the properties of several monofunctional materials such as photo-refractive, laser, luminescent, and plasmonic ones. Based on PTR glasses, various diffractive holographic elements and photonic devices were developed in both the volume and fiber versions. In this paper, the fabrication of optical planar waveguides on PTR glass by low-temperature ion exchange is reported for the first time. Planar waveguides were fabrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 32 publications
0
8
0
2
Order By: Relevance
“…Currently, phase holograms recorded in PTR glass are used as line-narrowing and stabilizing filters, spectral and spatial filters, compressors for femtoand picoseconds laser beams, spectral beam combiners, high-power beam splitters, etc. Although PTR glass was developed as a photosensitive medium for recording volume Bragg gratings, recent studies showed that it is a polyfunctional material that can combine the properties of holographic, laser, and photoetchable media [1,2,[5][6][7][8]. In this work, we demonstrate that the functionality of PTR glass matrix can be substantially extended via the formation of silver nanostructures inside the glass or on its surface.…”
Section: Introductionmentioning
confidence: 76%
“…Currently, phase holograms recorded in PTR glass are used as line-narrowing and stabilizing filters, spectral and spatial filters, compressors for femtoand picoseconds laser beams, spectral beam combiners, high-power beam splitters, etc. Although PTR glass was developed as a photosensitive medium for recording volume Bragg gratings, recent studies showed that it is a polyfunctional material that can combine the properties of holographic, laser, and photoetchable media [1,2,[5][6][7][8]. In this work, we demonstrate that the functionality of PTR glass matrix can be substantially extended via the formation of silver nanostructures inside the glass or on its surface.…”
Section: Introductionmentioning
confidence: 76%
“…на лазерных ФТР стеклах, активированных неодимом, эрбием и иттербием, получена генерация, что открывает возможности реализации в стекле идеологии монолитной интеграции брэгговских решеток и лазерной среды, по аналогии с полупроводниковыми лазерами с распределенной обратной связью [19,20].…”
Section: фото-терморефрактивные стеклаunclassified
“…Так, ФТР стекла содержат щелочную компоненту (ионы натрия), и к таким стеклам применима ионообменная технология, например, возможно заменять ионы натрия в ФТР стекле на ионы серебра, калия, рубидия, цезия из внешнего источника -расплава соли. Эта технология позволяет повышать показатель преломления ( n = 10 −3 ) на поверхности ФТР стекла и создавать ионообменные оптические Ag + , K + , Rb + и Cs + волноводы, а также упрочнять поверхность за счет сжимающих диффузионных напряжений[19].…”
unclassified
“…These ions can be changed on another monovalent ion (silver, potassium, rubidium, and cesium) by a well-known ion-exchange technique. This approach allowed us to fabricate ion-exchanged optical, luminescent, and plasmonic waveguides as well as to increase the mechanical, thermal, and optical resistance of the glass [20].…”
Section: Introductionmentioning
confidence: 99%